Relationship Between Mental Health, Competitive Aggression and Anger Rumination with Regard to the Role of Mental Health of Martial Arts Athletes in Gilan Province - Mortez Hazrati; Sevda Sheikhi Lisar; Mohammad Taghipour (Recent Trends in Sports, 2024)
Due to the phenomenon of championship in sports, athletes are always very thirsty to achieve the championship and go on the podium, and this factor can cause negative behaviors by athletes, one of which is competitive aggression. Therefore, the main purpose of this study is to investigate the relationship between mental health, competitive aggression and anger rumination with regard to the role of mental health of martial artists in Gilan province. This research is quantitative research according to the research approach, applied research according to the purpose and a descriptive research according to the method of data collection. Statistical population of unarmed martial arts athletes in six sports of karate (60 people), Taekwondo (60 people), Judo (50 people), Muay Thai (55 people), Sanda (45 people) and Kickboxing (70 people) in the province There are Gilan who have a history of sports activities in the national and regional championships. The sampling method in this study is stratified. The data collection tool in this study is a questionnaire and to evaluate the validity of the questionnaire, content validity and construct validity and also to evaluate the reliability of the questionnaire, Cronbach's alpha coefficient and combined reliability were used. SPSS software was used at the level of descriptive statistics and Smart PLS software was used for the inferential part. The results of structural equation modeling with partial least squares approach showed that there is a significant relationship between mental health, mental health and anger rumination with competitive aggression. Mental health is a minor mediator in the relationship between mental health, competitive aggression and rumination. According to the obtained results, it is suggested that the coach encourages the athlete to have commitment and team discipline in order to control his aggressive behaviors and prevent dismissal and injury to the team. This commitment athlete is given to the coach. On the other hand, if violence is allowed in sports, it is better to reinforce instrumental violence, not hostile violence, that is, harming the opponent should not be the goal.
Keywords: Anger Management; Competitive Aggression; Hostile Violence; Martial Arts; Sobel Test